Cephalopods of the world : (FAO, 2006)
This is the first of three volumes of the second edition of this catalogue which reviews six families: Nautilidae, Sepiidae, Sepiolidae, Sepiadariidae, Idiosepiidae and Spirulidae, with 23 genera and the 201 known species. It contains information on all families and genera, as well as illustrated keys to all taxa, with information under each species for valid modern systematic name and original citation of the species (or subspecies); main synonyms; English, French and Spanish FAO names for the species; illustrations of dorsal and ventral aspect of the whole animal (as necessary) and other distinguishing illustrations; field characteristics; diagnostic features; geographic and vertical distribution, including GIS map; size; habitat; biology; interest to fishery; local names when available; and a remarks section (as necessary) and literature. It also includes information on terminology and measurements, a glossary, an introduction with an updated review of the existing biological knowledge on cephalopods (including fisheries information and catch data for recent years) and a bibliography.